Transfection and homologous recombination involving single-stranded DNA substrates in mammalian cells and nuclear extracts. - Rauth, S (1986)
We have examined the ability of single-stranded DNA to participate in homologous recombination reactions in mammalian cells and nuclear extracts derived from them. We have inserted a fragment of the neo gene into the single-stranded DNA phage vector M13 mp11. The neo fragment was derived from a deletion derivative of the prokaryotic-eukaryotic shuttle vector pSV2neo. The resulting single-stranded DNA was mixed with a double-stranded deletion derivative of pSV2neo and tested for recombination in human cells, monkey cells, and nuclear extracts obtained from human cells. We were able to obtain recombinant molecules containing wild-type neo genes in all three systems. Examination of the products of recombination indicated that they resulted from correction of the deletion in the double-stranded DNA substrate. We were unable to detect any extensive conversion of single-stranded DNA into its double-stranded counterpart before it participated in the recombination reaction. We have also tested the ability of single-stranded DNA to yield transfectants. When a single-stranded DNA derivative of the herpes simplex virus thymidine kinase (TK) gene was introduced into mouse L-M(TK-) cells, we were able to obtain TK+ colonies. From these results, we conclude that single-stranded DNA can participate in transfection as well as homologous recombination reactions in mammalian cells.